Ladybird beetles fauna (Coleoptera: Coccinellidae) of the Republic of Mordovia, Russia - ALEXANDER B. RUCHIN; LEONID V. EGOROV; GENNADY B. SEMISHIN (Biodiversitas Journal of Biological Diversity, 2019)
Ruchin AB, Egorov LV, Semishin GB. 2019. Ladybird beetles fauna (Coleoptera: Coccinellidae) of the Republic of Mordovia, Russia. Biodiversitas 20: 316-327. The paper presents the first overview of Coccinellidae fauna of the Republic of Mordovia, Russia. Nowadays 46 species are reliably known in Mordovia. Of these, three species have firstly been registered in the Republic of Mordovia in recent years, namely Nephus bipunctatus, Hyperaspis erythrocephala, and Oenopia conglobata. In addition, three species were recommended to be excluded from the list of regional fauna.